Pemanfaatan Limbah Botol Plastik Sebagai Media Revitalisasi Greenhose MTsN 1 Kota Palangka Raya - Reski Saputra; Nanik Lestariningsih; Rita Sukaesih (Swadaya: Jurnal Pengabdian Masyarakat, 2025)
Purpose: The Greenhouse Revitalization activity at MTsN 1 Kota Palangka Raya aims to address the declining function of the school greenhouse as a learning facility and to reduce the accumulation of plastic bottle waste within the school environment. This program is also intended to integrate ethnopedagogical values and enhance students’ ecological awareness in realizing an environmentally conscious school. Methodology: The activity was implemented using a participatory project-based approach involving teachers, students, and the Magang Mengabdi team. The stages included coordination and preparation, material processing, and assembling and installing greenhouse walls made from used plastic bottles. This collaborative approach encouraged active participation from all school members throughout the implementation process. Findings: The results indicate that the program successfully revitalized the greenhouse’s function as a contextual learning medium while fostering students’ environmental awareness through the application of the 3R principles (Reduce, Reuse, Recycle). The use of plastic bottles provided functional, aesthetic, and educational value and became a simple innovation model that can be replicated in other schools. The activity also highlighted the essential role of school leadership and collaboration among the school community in supporting SDGs 4, 12, and 13, namely quality education, responsible consumption and production, and climate action.